Resourcing inclusive education - Goldan, Janka; Lambrecht, Jennifer; Loreman, Tim, 1970- (International perspectives on inclusive education, 2021)
While resource provision is widely recognized as an essential element of successful inclusive education, this is the first time an entire book has been dedicated to the topic. In this volume leading experts address international perspectives on funding models, the role of resources, and the development of professionals for the implementation of effective inclusive education. Split into two parts, the first section of the book addresses funding challenges that have emerged following the implementation of an inclusive school system. The authors present a broad range of international perspectives on different funding models and collate evidence from a variety of countries. They also unearth a variety of perceptions regarding resourcing for successful implementation of inclusive education. In the second part of the book, the authors focus on international perspectives of teacher training and professional development for inclusive education, ranging from early childhood education to post-secondary teacher training. Providing critical information and empirical studies, valuable to all of those engaged in the endeavour of providing adequate resources to support inclusive education, this volume is of interest to education policy makers, school and system leaders, and economists.